Intravascular Ultrasound–Guided Percutaneous Coronary Intervention: An Updated Review - Dhruv Mahtta; Islam Y. Elgendy (Cardiovascular Innovations and Applications, 2018)
Common practice dictates the performance of percutaneous coronary intervention under conventional angiographic guidance. With studies suggesting the high incidence of intraobserver variability, especially in angiographic borderline lesions, new modalities such as intravascular ultrasound (IVUS) guidance during percutaneous coronary intervention have surfaced. Multiple studies have shown improved outcomes with IVUS guidance, mainly driven by a decrease in ischemia-driven target lesion revascularization. In the past two decades, a multitude of studies have investigated the uses and clinical outcomes associated with this technology. In this review, we highlight the utility, advantages, economic implications, and clinical outcomes of IVUS guidance over standard angiographic guidance, with emphasis on data as they pertain to IVUS-guided stent implantation.